DAMPAK PERKEMBANGAN PENDIDIKAN ANAK KELUARGA TKW DI PROBOLINGGO - Abdul Hamid (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
Education is a learning, knowledge, skills, and habits of a group of people that are passed down from one generation to the next. Through teaching, training or research, education is also a science or teaching material that we can apply or teach to our students in order to achieve a good learning process. We can also apply education and we get it at home, in the school environment and in the community. In this case education is also very influential in life in the present and in the future. The development of children's education is very important for us to know so that the development of our children can develop properly so that they can grow according to what we expect. When a parent works as a TKW abroad, a child needs a role or someone else's figure to replace the parents in monitoring the development of their child's education. Thus, it is necessary to have a discussion that describes the Impact of the Educational Development of Children who are abandoned by their parents to become TKW. This study aims to describe the Impact of the Educational Development of the Children of TKW Families in Probolinggo City. This type of research is qualitative. Data obtained through interviews, observations, and field studies. The data show that the role of foster parents will have different impacts.